Do Different Measurements of Soil Quality Influence the Results of a Ricardian Analysis? - A Case Study on the Effects of Climate Change on German Agriculture - Eva Schmidtner; Stephan Dabbert; Christian Lippert (German Journal of Agricultural Economics (GJAE), 2015)
This study assesses the potential impact of future climate change on agricultural land rents in Germany using a Ricardian approach. In addition to including common explanatory variables, we focus on the effects of different indicators of soil characteristics when explaining land rental prices. The analysis is based on data from the official farm census 1999, weather data from the German National Meteorological Service and different soil data-bases at the county level. Different classifications of soil quality do not influence the results of our Ricardian analysis. The results of spatial error models indicate higher land rental prices for locations with more productive soils and higher mean annual temperatures. Also a lower land slope, a smaller share of rented land and (in some cases) less spring precipitation increase land rental prices. To estimate the effects of changing climatic conditions on future land rents, we draw on data from the regional climate model REMO for 2011-2040. Our models show an average land rent increase of 10-17% resulting from the expected changes in temperature and spring precipitation. According to our results future climate change will have an overall positive but spatially heterogeneous impact on the agricultural income in Germany.
Keywords: 330